1968
DOI: 10.1002/zaac.19683620306
|View full text |Cite
|
Sign up to set email alerts
|

Über Zirkonate, Hafnate und Thorate von Barium, Strontium, Lithium und Natrium

Abstract: Inhaltsiibersicht I n den Systemen MIIO/XIVO, (MI1 = Sr, Ba; XIv = Zr, Hf) existieren neben den Metaverbindungen basenreichere Verbindungen des Typs M:IXIVO, mit tetragonaler K,NiF,-Struktur. Eingehende Untersuchungen in den Systemen Li,O/X1vO, (XIV = Zr, Hf) fiihrten zur Darstellung und Charakterisierung der neuen Verbindungstypen Li4XIv0, und L&XIVO,. Tho, bildet mit Erdalkali-und Alkalioxiden nur Metaverbindungen, tritt jedoch mit Li,O uberhaupt nicht in Reaktion. Zwischen Na,ThO, und Li,ZrO, besteht nach d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…It is generally accepted that the room‐temperature crystal structure of BaHfO 3 can be described by a cubic unit cell; however, there are discrepancies concerning the unit cell length. For example, Scholder et al 27 reported a =4.171 Å, whereas Gooden and McCarthy 28 reported a =8.333 Å. The exact crystal structure of SrHfO 3 has also been a matter of some controversy.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the room‐temperature crystal structure of BaHfO 3 can be described by a cubic unit cell; however, there are discrepancies concerning the unit cell length. For example, Scholder et al 27 reported a =4.171 Å, whereas Gooden and McCarthy 28 reported a =8.333 Å. The exact crystal structure of SrHfO 3 has also been a matter of some controversy.…”
Section: Introductionmentioning
confidence: 99%
“…The partial substitution of Sr by Ba, namely Sr x Ba 1−x HfO 3 , produces a series of new compounds where there is a competition between Sr-O and Ba-O bonds due to the different ionic radius and valence electrons. At minor temperature, a lower symmetry structure in the shape of a distorted cubic arrangement can be found [7][8][9]. Kennedy et al [10] also described the symmetry of Sr 0.5 Ba 0.5 ZrO 3 at room temperature as orthorhombic in Imma, and noted that only a small increase in the Ba content was sufficient to induce a transition to the tetragonal structure.…”
Section: Introductionmentioning
confidence: 94%
“…At temperatures in excess of 1400 • C, the existence of four binary oxide phases was reported: SrZrO 3 , Sr 4 Zr 3 O 10 , Sr 3 Zr 2 O 7 and Sr 2 ZrO 4 [18][19][20][21][22]. According to calculated phase diagram sections [23,24], the Sr 4 Zr 3 O 10 , Sr 3 Zr 2 O 7 and Sr 2 ZrO 4 phases are expected to be stable down to at least 725 • C. However, the experimental study of Tilloca and Perez y Jorba [22] demonstrates that only the SrZrO 3 phase is stable at 900 • C in air.…”
Section: Sro-zromentioning
confidence: 99%
“…The SrO-TiO 2 system was studied by Drys and Trzebiatowsi [16] as well as by Cocco and Massazza [17] although at temperatures in excess of 1200 • C. Similarly, several authors have studied the SrO-ZrO 2 system, but mostly at temperatures higher than 1400 • C [18][19][20][21], with the exception of Tilloca and Perez y Jorba [22], who extended their investigations down to 1000 • C. For this system, calculated phase equilibria are also available [23,24]. The SrO-HfO 2 system was studied in details by Shevchenko et al [25] and by Delamarre [26] at temperatures higher than 1600 and 1250 • C, respectively.…”
Section: Introductionmentioning
confidence: 99%